Mobilization of electroosmotic flow markers in capillary zone electrophoresis. Issue 7 (19th February 2021) - Martínková, Eva; Křížek, Tomáš; Kubíčková, Anna; Coufal, Pavel
Abstract: UV‐absorbing neutral substances are commonly used as markers of mean electroosmotic flow in capillary electrophoresis for their zero electrophoretic mobility in an electric field. However, some of these markers can interact with background electrolyte components and migrate at a different velocity than the electroosmotic flow. Thus, we tested 11 markers primarily varying in their degree of methylation and type of central atom in combination with five background electrolyte cations differing in their ionic radii and surface charge density, measuring the relative electrophoretic mobility using thiourea as a reference marker. Our results from this set of experiments showed some general trends in the mobilization of the markers based on the effects of marker structure and type of background electrolyte cation on the relative electrophoretic mobility. As an example, the effects of an inadequate choice of marker on analyte identification were illustrated in the electrophoretic separation of glucosinolates. Therefore, our findings may help electrophoretists appropriately select electroosmotic flow markers for various electrophoretic systems.